2008
DOI: 10.2337/db07-1376
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Arteriolar Narrowing Predicts Incidence of Diabetes

Abstract: OBJECTIVE—To examine the relationship of retinal vascular caliber to incident diabetes in a population-based cohort. RESEARCH DESIGN AND METHODS—The Australian Diabetes, Obesity and Lifestyle (AusDiab) Study recruited adults aged 25+ years across Australia in 1999–2000, with a follow-up 5 years later in 2004–2005. Participants' glycemic status was classified using fasting plasma glucose (FPG) and 2-h oral glucose tolerance (2-h plasma glucose [2hPG]) tests. Diabetes was diagnosed if FPG was ≥7.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 27 publications
4
58
0
Order By: Relevance
“…All articles were published in English after 1994. We found 15 prospective population-based cohort studies, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] 3 prospective nested case-control studies, [31][32][33] and 5 prospective case-cohort studies. [34][35][36][37][38] The studies examined mainly white participants from Europe, the United States, and Australia.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…All articles were published in English after 1994. We found 15 prospective population-based cohort studies, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] 3 prospective nested case-control studies, [31][32][33] and 5 prospective case-cohort studies. [34][35][36][37][38] The studies examined mainly white participants from Europe, the United States, and Australia.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…20,21,24,29,30 Table I in the online-only Data Supplement shows a higher incidence of T2DM with smaller baseline arteriolar diameters and AVR. In contrast, venular diameters were not significantly associated with the incidence of T2DM.…”
Section: Microvascular Dysfunction and Risk Of T2dmmentioning
confidence: 99%
“…Recent studies show that structural retinal microvascular changes, such as the presence of retinopathy or variations in retinal vascular caliber, are predictive of a range of systemic and ocular conditions, such as diabetes, stroke, coronary heart disease and heart failure, and diabetic retinopathy. [1][2][3][4][5][6][7] It has been hypothesized that dilation of retinal vessels in response to diffuse luminance flicker may reflect intrinsic endothelial function, 8 mediated possibly by nitric oxide. [9][10][11][12] Thus, such measurements may allow in vivo quantification of retinal endothelial function, which may help in understanding the physiological and pathological alterations of retinal microcirculation in various ocular and systemic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, largely in white populations, have shown that one particular retinal vascular change-retinal vascular caliber (diameter)-is a marker of early microvascular damage related to diabetes and associated complications (e.g., DR, nephropathy, and cardiovascular disease). [4][5][6][7][8][9][10][11][12][13] The human circulatory system is believed to conform to an optimum design principle, 14 which allows sufficient blood distribution with the least amount of energy. Deviation from this optimal architecture therefore results in suboptimal and less efficient peripheral circulation.…”
Section: Introductionmentioning
confidence: 99%